(untitled) (CIPEEX, 2026)
The incorporation of immersive digital technologies, particularly Virtual Reality (VR), presents a transformative potential for teaching in Civil Engineering and Architecture, promoting active learning and spatial visualization experiences that are not achievable in traditional environments. This study implements virtual models of Blocks A, B, and C of the UniEVANGÉLICA campus and evaluates the pedagogical and technical feasibility of using VR as a support tool for teaching and collaborative student interaction. The methodology combined architectural modeling in Autodesk Revit, conversion and adaptation of the models into interactive 3D environments, and deployment via the Mozilla Hubs platform. On-site surveys, model processing (texturing and web optimization), and pilot tests with students and professors were carried out. Preliminary results indicate improvements in spatial understanding and collaborative engagement, as well as technical challenges resulting from the discontinuation of the platform, which were overcome through the development of local infrastructure. It is concluded that campus virtualization represents a promising resource to expand practical and collaborative experiences, with recommendations for continued technical refinement, curricular integration, and extended evaluation.